TO THE QUESTION OF CLASSIFICATION AND TREATMENT TACTICS OF HYPERSPLENISM PORTAL GENESIS IN CHILDREN - V. A. Tarakanov; A. V. Poleev; O. A. Tereshenko; A. E. Strykovsky (Кубанский научный медицинский вестник, 2017)
The paper presents the experience in the treatment of 128 children with the syndrome of portal hypertension (SPH) from 1997 to 2013. Hypersplenism (HS) was diagnosed in 48 children (37,5%). Applied methods of medical and surgical treatment of HS. The authors of the HS divides into three forms clinical course: 1) compensated, 2) subcompensated and 3) decompensated. Compensated form of HS diagnosed in 19-and children (14,8%) and given medical treatment. Subcompensated form detected in 19 patients (14,8%) and requires both medical and surgical treatment. Decompensated form HS exhibited 10 patients (7,8%) was cured surgical method.